Dampak Sistem Kasta terhadap Struktur Sosial Umat Buddha di Bali - Sumitra Dewi; Jo Priastana; Edi Priyono (Dhammavicaya : Jurnal Pengkajian Dhamma, 2024)
This research is to find out how the impact of the caste system in Bali on the life of the Buddhist community. In this study the method used is a qualitative research method with descriptive research results. Buddhism has been known to the Balinese people since ancient times, but in harmony with the development of Hinduism so that they were united into Shiva-Buddha. Balinese Hinduism does not use Indian Hindu culture, but the Balinese Hindu community adheres to their own culture, namely the customs of their ancestors and modern life systems. The Balinese Hindu community always carries out the Menyama Braya concept (the concept of living in harmony and respecting each other in terms of culture and differences) which has been running for generations The social structure of Buddhists in Bali is divided into gharavasa and pabbajita. Buddhists in Bali practice the teachings of the Great Teacher of Buddha, so they are not affected by the caste system that exists in social life. Buddhists in Bali promote tolerance between religions. Behaviorally, Buddhists in Bali have never adhered to the caste system or degree of social status in their daily life and always practice the teachings of Buddha Dhamma. But the Balinese Buddhist community still respects the traditions that apply in Balinese customs. In essence, the relationship between Hindus and Buddhists in Bali is not a problem at all. Because everyone respects each other. And no influence in caste either from family, education, work, marriage, and most importantly all good in thought, speech and behavior.